Cost-Effective Critical Care: Cost Containment and Rationing - Rubenfeld, Gordon D. (Seminars in Respiratory and Critical Care Medicine, 2012)
Rationing occurs whenever the demand for a good or service exceeds its supply. Therefore rationing is an inevitable occurrence in medicine and in critical care where the potential demand for effective medical care will exceed supply. Although there are many strategies to allocate medical resources one that is often considered is based on cost-effectiveness. Cost-effectiveness analysis attempts to estimate the value of individual medical treatments in terms of dollars and outcomes. Allocation of medical treatments based on cost-effectiveness analysis requires valid estimates of both the costs and the effectiveness of treatments as well as some overarching body with the authority to enforce allocation based on these analyses.Limitations of allocation based on cost-effectiveness analysis in critical care include difficulties in estimating marginal costs of critical care treatments, limited evidence for any treatments with efficacy, and the ethical principle of rescuing identifiable lives in imminent risk of death. The prospect of a pandemic influenza-like infection has stimulated a lot of interest in hypothetical rationing strategies for the intensive care unit, none of which has been tested in actual pandemic scenarios. Given the burden of critical illness and the wide variation in resources a global approach to rationing is untenable. The article concludes with a vision of the future of allocation in critical care.
Keywords: cost containment; rationing; critical care; ethics; resources